PENGARUH VARIASI KONSENTRASI CROSPOVIDONE SEBAGAI SUPER DISINTEGRAN TERHADAP MUTU FISIK ORAL FAST DISSOLVING TABLET - Yugo Susanto (AFAMEDIS, 2023)
Ondansetron HCL is a 5-HT3 (serotonin) receptor antagonist drug which was recently introduced as an anti-vomiting drug. Ondansetron HCL is available in the form of 4 mg tablets. .The manufacture of OFDT ondansetron HCL in this formulation was to find out which results were more optimal than the different concentrations of crospovidone disintegrant with concentrations of 2%, 3%, and 4%. Oral Fast Dissolving Tablet (OFDT) are solid drug tablets that are easily disintegrated when placed on the tongue and can provide a rapid therapeutic effect. This study aims to determine the concentration of crospovidone on the physical quality of Oral Fast Dissolving Tablet. The method used in this research is experimental. Three different formulations were tested. The maximum wevelength of ondansetron HCl is 248nm. The concentrations used in the calibration of ondansetron HCl were 6 ppm, 8 ppm, 10 ppm, 12 ppm, 14 ppm, 16 ppm and 18 ppm. The results obtained were tested using SSPSS one way anova. In this study, the independent variables were several rations of crospovidone concentration, namely 2%, 3% and 4%.